PENGARUH JENIS OLI TERHADAP KONSUMSI BAHAN BAKAR PADA KENDERAAN RODA DUA 125 CC - Tambos August Sianturi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
Machine oil’s variety affects the consumption of the vehicle’s fuel. Oil can be divided based on its viscosity. This research aims at analyzing the effect kinds of oil on the consumption of the vehicle’s fuel. The difference of lubricants’ viscosity is shown by the specification of machine oil on a tester-motorcycle with SAE 10W40, SAE 15W40, 20W40. Vehicle used as a tester is a 125 cc motorcycle. The measurement of fuel’s consumption was done by arranging the rotation of machine by using tacho meter on rotation 1000 rpm, 2000 rpm, 3000 rpm and 4000 rpm, and consumption of fuel itself was measured by measuring cup. The research’s findings are : oil with SAE 10W40 and 15W40 and 20W40 on rotation 1000 rpm, 2000 rpm, 3000 rpm and 4000 rpm affect the consumption of machine’s fuel in which oil with SAE 10W40 is more economical on rotation 1000 rpm, 2000 rpm, 3000 rpm, and 4000 rpm meanwhile on rotation 4000 rpm oil with SAE 10W40 is more economical; on rotation 2000 rpm the lowest value of fuel’s consumption is 0.35 ml/m oil with SAE 10W40; on rotation 3000 rpm lowest value of fuel’s consumption is 0.65 ml/m oil SAE 10W40; AND ON ROTATION 4000 rpm lowest value of fuel’s consumption is 0,9 ml/m oil with SAE 15W40.